Biodemography of Fertility in Japan - Konishi, Shoko (Population Studies of Japan,, 2018)
This book presents original data on the proximate determinants of fertility in Japan. Its goal is to disaggregate low fertility levels in Japan into physiological, behavioral, and social components. Further, the book reviews previous studies on the proximate determinants of fertility in Japan, and compares the data to that on other countries. This book is the first to summarize previous research projects conducted in Japan on this topic, and proposes future research directions to fill the remaining research gaps. Further, it sheds new light on the similarities and differences between the fertility level in Japan and in other countries in terms of biodemographical components, helping readers understand the mechanisms of fertility change in Japan.